Application of uti possidetis juris principle in the process of determination of international borders - Tubić Bojan (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2011)
Uti possidetis juris principle was basic rule in determining international borders in the period of decolonization. It was applied in Latin America and Africa, but also at the end of 20th century in the processes of dissolution of USSR, SFRY and Czechoslovakia. Uti possidetis juris principle is based on the presumption that former colonial administrative borders kept stability and territorial integrity. It was undoubtedly connected with the right of self-determination. It keeps the existing borders by preventing secession, but in that way it does not solve the problem of badly determined and disputed borders. The unclear foundations on which the borders were determined can be a source of chaos and indisputes, which was shown n some cases before the International Court of Justice. The dominant theory is that uti possidetis juris principle should be applied with certain limitations, in the period after decolonization as a basis for preserving the territorial integrity of postcolonial states.